2004
DOI: 10.1081/drt-200025626
|View full text |Cite
|
Sign up to set email alerts
|

Heat Recovery from Dryer Exhaust Air

Abstract: The classical problem of heat recovery from convective dryer exhaust air is considered under modern easy-to-programming techniques towards effective decision making environment. Heat exchangers as well as heat pumps are considered versus various dryer performance characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 9 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Regarding the latter, several methods have been developed to improve energy saving during drying, including heat recovery with [8,9] and without [10] flue gas recirculation, heat pumps [11,12], pinch technology [13], and mechanical vapor recompression (MVR) [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, several methods have been developed to improve energy saving during drying, including heat recovery with [8,9] and without [10] flue gas recirculation, heat pumps [11,12], pinch technology [13], and mechanical vapor recompression (MVR) [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The acquired experimental data is used for the calculation and analysis of dryer efficiency. The data acquired from all the sensors can be 18 plotted on screen at the top left corner of the interface. A photograph of the prototype platform is shown in Figure 8.…”
Section: User Interfacementioning
confidence: 99%
“…[7] Krokida and Bisharat found that drying efficiency of tumble-dryers could reach 79% by simultaneously using heat pump and heat exchanger. [18] The reported research is mainly devoted to introducing new technologies such as additional recirculation system of exhaust air and microwave heating, and optimization of drying parameters to achieve better drying efficiency, but in all these studies, the drying process is considered as a single drying stage. However, the moisture removal rate of fabric, the surface temperature and instantaneous moisture content of fabric, the temperature and humidity of drying air are all continuously changing during the drying process.…”
mentioning
confidence: 99%
“…A VHR unit designed to recover heat from the exhaust air flow of homes was adapted to recover heat from the exhaust stream of a low cost food dehydrator. The efficiency of the energy recovery from an exhaust stream depends on the change in performance of the dehydrator which is based on the energy utilized for the drying process [1]. The recovered heat from the exhaust stream can be used to pre heat fresh air.…”
Section: Introductionmentioning
confidence: 99%